Flowers4U.co.za : satisfaction infraction - Beswick, Claire; Saini, Yvonne (London : Wits Business School, 2018)
On 17 February 2017, Thomas Quinn, the managing director of online florist, Flowers4U.co.za, received an irate email from one of his clients. The client was still not satisfied with a solution he had proposed the day before to make up for unmet expectations regarding flowers delivered on Valentines' Day. Quinn wondered how best to respond.
Originally Published InBeswick, C., & Saini, Y. (2018). Flowers4U.co.za: Satisfaction infraction. WBS-2017-5. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Quinn, Thomas; Flowers4U.co.za.; Consumer satisfaction; Florists